SISTEM IPLEMENTASI PEMBELAJARAN BERBASIS BOARDING SCHOOL TERHADAP PENINGKATAN KOMPETENSI SISWA Di MTs N 1 KOTA BIMA - Putri, Kiki Afriani; Maidarfrida, Maidarfrida; Trimansyah, Trimansyah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2024)
A boarding school is an educational institution that accommodates all students who are members of it because that way coaches and educators can easily control and manage it. This research aims to find out how the boarding school-based learning implementation system improves student competency. The research method used is qualitative research with a phenomenological approach, with data collection techniques through observation, interviews, documentation and analyzing literature. The results of this research found that the learning system carried out was that there was a learning time program grouped into daily activities, weekly activities, monthly activities and also annual activities. This activity program contains various learning processes that are sure to have great potential in improving student competency. The learning system applied at boarding schools has the best method which implements learning balance, provides adequate facilities to realize and support a good learning process, and creates a pleasant learning atmosphere.